Chromatin exposes intrinsic differences in the transcriptional activities of estrogen receptors α and β - Cheung, Edwin (Oxford University Press, 2003)
The biological actions of estrogens are mediated via two distinct intranuclear estrogen receptor (ER) proteins, ERα and ERβ. We have used an in vitro chromatin assembly and transcription system to compare the transcriptional activities of the two ERs in the context of chromatin, the physiological template for transcription by RNA polymerase II. We find that under conditions where many biochemical activities of the receptors are similar (e.g. ligand binding, chromatin binding, chromatin remodeling and co-activator recruitment), liganded ERα is a much more potent transcriptional activator than ERβ with chromatin templates, but not with naked DNA. This difference is attributable to the N-terminal A/B region of ERα, which contains a transferable activation function that facilitates transcription specifically with chromatin templates. Interestingly, chromatin selectively restricts ligand-dependent transcriptional activation by ERβ under some conditions (e.g. with a closed chromatin architecture), while allowing it under other conditions (e.g. with an open chromatin architecture). Collectively, our results define an important role for chromatin in determining signaling outcomes mediated by distinct subtypes of signal-transducing transcriptional activator proteins.